2014
DOI: 10.1007/s11816-014-0335-2
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the rice basic leucine zipper transcription factor OsbZIP12 confers drought tolerance to rice and makes seedlings hypersensitive to ABA

Abstract: Abiotic stresses such as drought, high salinity, and cold are key factors in determining crop yield. Rice is a notoriously drought-susceptible crop due in part to its small root system. Abscisic acid (ABA) involves in abiotic stress resistance in plants. The basic leucine zipper (bZIP) transcription factors play important roles in the ABA signaling pathway in plants. OsbZIP12 is a member of the group E bZIP transcription factor family in rice (Oryza sativa). Expression of OsbZIP12 is induced by abiotic stresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 43 publications
0
40
0
Order By: Relevance
“…AtbZIP10-LSD1 regulates basic defence and cell death in Arabidopsis thaliana after infection [60]. In rice, OsbZIP12 is a positive regulator of ABA signalling, conferring ABA-dependent drought tolerance [61]. And OsbZIP23 and OsbZIP72 also increase drought resistance through the ABA pathway [29,62].…”
Section: Evolution Of Itfbzip Genesmentioning
confidence: 99%
“…AtbZIP10-LSD1 regulates basic defence and cell death in Arabidopsis thaliana after infection [60]. In rice, OsbZIP12 is a positive regulator of ABA signalling, conferring ABA-dependent drought tolerance [61]. And OsbZIP23 and OsbZIP72 also increase drought resistance through the ABA pathway [29,62].…”
Section: Evolution Of Itfbzip Genesmentioning
confidence: 99%
“…These TFs are likely to bind to the corresponding cis-elements and co-regulate the expression of Os-NAC6 that participate in the ABA induction pathway and abiotic stress response in plants. In the bZIP family, the gene encoding OsbZIP12 was also found to have MYBRS, MYCRS, and W-box motifs in its promoter region, which can be recognized by TFs MYB, MYC, and WRKY, respectively [34]. Besides, OsNAC5 and OsbZip23 might co-regulate the expression of the downstream gene OsLEA3 since both of them enhance the transcription level of OsLEA3 [35].…”
Section: Plant Hormone Crosstalk In Drought Relevant Regulatory Pathwaysmentioning
confidence: 99%
“…In maize, ZmbZIP37, -17, and -112 showed high expression levels in drought stress conditions [88,89] and the overexpression of ZmbZIP72 enhanced the drought tolerance in transgenic Arabidopsis [90]. In rice, OsbZIP12 [34], -16 [91], -23, -45 [92], -71 [25], and -72 [93] play a positive role in drought tolerance through ABA signal, while OsbZIP52 [24] and -46 [94] were suggested to be a negative regulator in water deficiency. In wheat, the gene encoding TabZIP60 was highly induced by salt, cold, and ABA, and the overexpression of TabZIP60 enhanced the drought and frost tolerance in transgenic Arabidopsis [84].…”
Section: Bzip Familymentioning
confidence: 99%
“…Several studies have shown that overexpression of droughtresponsive transcription factors can lead to enhanced drought resistance. For example, plants overexpressing Arabidopsis (Arabidopsis thaliana) AtMYB96 or HARDY (an AP2/ERF transcription factor) or transgenic rice (Oryza sativa) lines overexpressing OsAP37, OsNAC5, OsNAC9, OsNAC10, OsbZIP12, OsbZIP12, or OsbZIP23 all showed strong resistance to drought stress (Karaba et al, 2007;Oh et al, 2009;Jeong et al, 2010Jeong et al, , 2013Seo et al, 2011;Redillas et al, 2012;Joo et al, 2014;Park et al, 2015). Drought-responsive genes are often categorized into abscisic acid (ABA)-dependent or ABAindependent groups.…”
mentioning
confidence: 99%